Analysis of the Influence of Organizational Culture, Remuneration, and Job Satisfaction on the Performance of Education Personnel - Rahmad Isa Masri; Sukarman Purba; Rosnelli Rosnelli (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of this research is to determine: a description of the organizational culture profile and remuneration system; organizational culture influences the performance of education personnel; the remuneration system affects the performance of education personnel; the influence of the work environment on the performance of education personnel; and the influence of organizational culture, remuneration, and work environment simultaneously on the performance of education personnel. The research approach uses an associative approach. The research was conducted at the Medan Aviation Polytechnic. The research results show: (1) there are anomalies in the application of remuneration at the Medan Aviation Polytechnic; (2) individual organizational culture shows an unstandardized coefficient beta value of 0.531 and shows a significant value of <0.05, then H1 is accepted. Thus, organizational culture influences performance; (3) remuneration testing shows an unstandardized coefficient beta value of 0.248 and a significant value of <0.05, so H2 is accepted. Thus, remuneration influences performance; (4) if the unstandardized coefficient beta value is 0.135 and shows significance at <0.05, then H3 is accepted. Thus, job satisfaction influences performance; (5) the individual influence of organizational culture on performance with job satisfaction as an intervening variable shows unstandardized beta coefficients of 0.000 and shows significance at <0.05, as well as the influence of remuneration with job satisfaction as an intervening variable shows a significance <0.05. Thus, it can be concluded that organizational culture and remuneration variables influence performance by intervening with job satisfaction.